1999
DOI: 10.1159/000024657
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Evaluation of Asbestos Air Concentrations

Abstract: Both area and personal air samples collected during an asbestos abatement project were matched and statistically analysed. Among the many parameters studied were fibre concentrations and their variability. Mean values for area and personal samples were 0.005 and 0.024 f·cm–3 of air, respectively. Summary values for area and personal samples suggest that exposures are low with no single exposure value exceeding the current OSHA TWA value of 0.1 f·cm–3 of air. Within- and between-worker ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
78
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(91 citation statements)
references
References 64 publications
(238 reference statements)
13
78
0
Order By: Relevance
“…It has been suggested that summary exposure data be reported as arithmetic mean (AM), geometric mean (GM), standard deviation (SD), geometric standard deviation (GSD) and range [2][3][4]. In the aforementioned article, some of these descriptors were provided.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that summary exposure data be reported as arithmetic mean (AM), geometric mean (GM), standard deviation (SD), geometric standard deviation (GSD) and range [2][3][4]. In the aforementioned article, some of these descriptors were provided.…”
mentioning
confidence: 99%
“…It has been generally accepted that environmental (area) and occupational (personal) exposure concentration distributions are nonnormal with most having a logarithmic form [2][3][4][7][8][9][10]. Previous investigations of formaldehyde exposure [10][11][12] suggest that concentrations of this chemical (exposure) follow a nonnormal distribution, which is most likely lognormal.…”
mentioning
confidence: 99%
See 3 more Smart Citations